2021
DOI: 10.1017/s135561772100103x
|View full text |Cite
|
Sign up to set email alerts
|

Screening Tools for Cognitive Impairment in Adults with Substance Use Disorders: A Systematic Review

Abstract: Objectives: Cognitive impairment is common in individuals with substance use disorders (SUDs), yet no evidence-based guidelines exist regarding the most appropriate screening measure for use in this population. This systematic review aimed to (1) describe different cognitive screening measures used in adults with SUDs, (2) identify substance use populations and contexts these tools are utilised in, (3) review diagnostic accuracy of these screening measures versus an accepted objective reference standard, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 61 publications
1
11
0
Order By: Relevance
“…The most studied tool was the MoCA; it demonstrated the most consistent ability to detect cognitive impairment in this population. Other measures (ACE-R, BEARNI and BEAT) showed promise for use but require further studies before recommending their implementation in clinic (Ko et al, 2021).…”
Section: Screening Testsmentioning
confidence: 99%
See 2 more Smart Citations
“…The most studied tool was the MoCA; it demonstrated the most consistent ability to detect cognitive impairment in this population. Other measures (ACE-R, BEARNI and BEAT) showed promise for use but require further studies before recommending their implementation in clinic (Ko et al, 2021).…”
Section: Screening Testsmentioning
confidence: 99%
“…Folstein mini-mental state examination (MMSE) (Folstein et al, 1975;Ko et al, 2021) 30-item instrument Assesses orientation to time and place, registration, attention, concentration, recall, language, repetition and complex commands Screens for Alzheimer's and other types of dementia Disadvantage: may be culturally biased, failed to demonstrate adequate classification accuracy in the context of SUDs Addenbrooke's cognitive examinationrevised (ACE-R) (Ridley et al, 2018) Assesses attention, orientation, memory, language, verbal fluency and visuospatial skills Useful in detecting cognitive impairment in the context of SUDs Montreal cognitive assessment (MoCA) (Hobson, 2015;Copersino et al, 2012) 30-item instrument Assesses short-term memory recall, visuospatial abilities, executive functions, attention, concentration, working memory, language, abstract reasoning and orientation to time and place Has good specificity (87%) and sensitivity (90%). More sensitive than MMSE in assessing mild-to-moderate cognitive impairment Detects cognitive impairment in the context of substance use Predicts clinically relevant behaviors among older adults with SUDs Disadvantage: may have cultural and educational biases Mini-Cog (Borson et al, 2000) Brief screening tool for mild cognitive impairment in older adults Has good sensitivity, specificity and negative predictive value Consists of three main steps: !…”
Section: Table 4 Validated Screening Tools For Neurocognitive Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Through a combination of formal literature searches and reference mining of identified sources, we identified 50 references: Nine were excluded at citation screening; nine were excluded because they pertained to settings that were not relevant to the patient population or to primary care settings, did not mention cognitive assessment, or did not address assessment of CI; and ten provided background. Nineteen studies reported in 22 publications (guidelines and peerreviewed reports of studies) that addressed screening patients for CI in some way were used (American Academy of Family Physicians [AAFP], 2014; American Psychological Association, 2021; Aufill et al, 2019;Burton et al, 2021;CMS, 2022;Chen et al, 2018;Chow and MacLean, 2001;Cordell et al, 2013; Dementia Warning Signs Workgroup, Office of Geriatrics and Extended Care, and the National Center for Health Promotion and Disease Prevention, 2011;Feil, MacLean, and Sultzer, 2007;Fernandes, Goodarzi and Holroyd-Leduc, 2021;Ko et al, 2022;Koekkoek et al, 2016;LeRoith et al, 2019;Levell-Smith, 2020;Medicare Learning Network, 2021;Mini-Cog, 2016;Paraizo et al, 2016;Petersen et al, 2018;Thompson et al, 2021;Tokuhara et al, 2006;USPSTF et al, 2020). Figure 4.1 shows the PRISMA flowchart for the items that were identified.…”
Section: Web-based Resourcesmentioning
confidence: 99%
“…A 2021 systematic review assessed screening tools for CI specifically for use in patients with SUD (high quality as assessed by AMSTAR 2) (Ko et al, 2022). Fourteen studies that met inclusion criteria identified ten cognitive screening tools.…”
Section: Systematic Reviewsmentioning
confidence: 99%